O definiciji površine - Drinovec-Drnovšek, Barbara (Obzornik za matematiko in fiziko, 2015)
We present an example published by H. A. Schwarz which shows that the area of a surface cannot be defined as the supremum of areas of all approximating polyhedral surfaces.
Keywords: dolžina; surface; površina; area; polyhedral surfaces; aproksimacija; approximation; poliedrske ploskve